Improving the Dynamic Mechanical Properties of XNBR Using ILs/KH550-Functionalized Multilayer Graphene - Chen, Duoli (Materials (Basel), 2019)
Graphene has been considered an ideal nanoscale reinforced phase for preparing high-performance composites, but the poor compatibility and weak interfacial interaction with the matrix have limited its application. Here a highly effective and environmentally friendly method for the functionalization of graphene is proposed through an interaction between as-exfoliated graphene and (3-aminopropyl) triethoxysilane (KH550), in which 1-butylsulfonate-3-methylimidazolium bisulfate (BSO(3)HMIm)(HSO(4)) ionic-liquids-modified graphene was prepared via an electrochemical exfoliation of graphite in (BSO(3)HMIm)(HSO(4)) solution, then (BSO(3)HMIm)(HSO(4))-modified graphene as a precursor was reacted with amine groups of KH550 for obtaining (BSO(3)HMIm)(HSO(4))/KH550-functionalized graphene. The final products as filler into carboxylated acrylonitrile‒butadiene rubber (XNBR) improve the dynamic mechanical properties. The improvement in the dynamic mechanical properties of the nanocomposite mainly depends on high interfacial interaction and graphene’s performance characteristics, as well as a good dispersion between functionalized graphene and the XNBR matrix.